AI-Powered Performance Appraisal: Balancing Automation with Human Judgment in Performance Management Systems - Taryana, Taryana (Pascasarjana STIE Amkop Makassar, 2025)
The integration of artificial intelligence (AI) into performance appraisal systems is transforming how organizations assess and manage employee performance. This study presents a literature-based review exploring the dynamic interplay between AI-driven automation and human judgment in performance management. Five key themes emerge from the review: efficiency and standardization, bias and fairness, human oversight and trust, ethical and psychological impacts, and the need for human-AI collaboration. Through real-world cases, including examples from Indonesian companies such as Gojek and Tokopedia, the study illustrates both the benefits and limitations of AI applications in appraisal systems. The findings highlight the importance of maintaining human involvement in decision-making to ensure fairness, contextual understanding, and ethical accountability. The paper concludes with recommendations for hybrid models that combine algorithmic insights with managerial discretion, advocating for transparent, fair, and adaptive systems of performance evaluation. Keywords: Artificial Intelligence (AI); Performance Appraisal; Evaluation; HR Technology